PERANAN PEMERINTAH DESA SUKANALU, KECAMATAN BARUSJAHE, KABUPATEN KARO DALAM UPAYA PELESTARIAN SITUS MERIAM PUNTUNG SEBAGAI OBJEK WISATA SEJARAH. - Tasya Gus Defany Br Purba Tambak; Sintia Juita Tarigan; Lestari Dara Cinta Utami Ginting; Nurhabsyah (Bajang Institute, 2023)
Puntung cannon is one of the cultural heritages in Sukanalu Village, Barusjahe District, Karo Regency, North Sumatra. The Puntung cannon site is visited by many people from inside andoutside the regions in Indonesia and even some from abroad with different purposes. As for the purpose, namely, for education, tourism, and even some for pilgrimage, which is said that if we pray at the Puntung cannon site not long after the prayer will be granted. This research uses the historical method with four stages, namely Heuristics, Criticism, Interpretation, Historiography. This research aims to find out how the development of the Puntung Cannon site and how the role of the government and the community in maintaining the Puntung Cannon site, where it turns out that the role of the government towards this site has not been fully carried out, because this site has not been included in the Cultural Heritage.